The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11071-017-3484-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of predictive control performance using fractal measures

Abstract: This paper presents novel approach to the task of control performance assessment. Proposed approach does not require any a priori knowledge on process model and uses control error time series data using nonlinear dynamical fractal persistence measures. Notion of the rescaled range R/S plots with estimation of Hurst exponent is applied. Crossover phenomenon is observed in data being investigated and discussed. Paper starts with industrial engineering rationale. Review of the control error histogram is followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 45 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…Esta cantidad invariante intrínseca del sistema tiene una relevancia singular para la caracterización de la previsibilidad. Los valores más altos de h implican valores más bajos de la predictibilidad 1/h, es decir, cuanto más caótico, menos predecible (Domański & Ławryńczuk, 2017).…”
Section: Exponentes De Lyapunovunclassified
“…Esta cantidad invariante intrínseca del sistema tiene una relevancia singular para la caracterización de la previsibilidad. Los valores más altos de h implican valores más bajos de la predictibilidad 1/h, es decir, cuanto más caótico, menos predecible (Domański & Ławryńczuk, 2017).…”
Section: Exponentes De Lyapunovunclassified
“…Non-Gaussian statistical [157] and fractal [158] methodologies have been investigated for the GPC predictive control algorithm. Linear [159] and nonlinear [160] DMC predictive control have been assessed using integral, statistical, information, and fractal measures.…”
Section: Data-driven Approachesmentioning
confidence: 99%
“…It has been shown that even simple linear MPC configuration requires alternative CPA approach, such as fractal [48] or non-Gaussian [6]. Nonlinear industrial control generates even more serious challenges for reliable MPC monitoring.…”
Section: Introductionmentioning
confidence: 99%